Analisis Penerapan Strategi Segmenting, Targeting dan Positioning Terhadap Tabungan Haji Pada Bank Tabungan Negara Syariah KC Bekasi - Fajriyah Salsabila Halim; Purnama Putra (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study is to analyze how the implementation of segmenting, targeting and positioning strategies for Hajj savings at the State Savings Bank Syariah KC Bekasi. This type of research is qualitative research using a phenomenological approach. The method used in data collection is primary data and secondary data with the methods of interview, observation, focus group discussion (FGD) and documentation. The results of this study indicate that the segmenting strategy applied to Tabungan Haji is geographic segmentation and demographic segmentation. The targeting strategy applied to Hajj Savings is using the Concentrated Market approach. The positioning strategy applied to Tabungan Haji is positioning products based on attributes, product users as well as price and quality. The obstacles faced include: (1) Lack of competent human resources (2) lack of public understanding (3) competition from other banks (4) external factors of the covid-19 pandemic. Solutions that can be done include: (1) conducting training for employees (2) conducting direct promotions to customers (3) utilizing technology (4) digitizing the application of the system